Liquidity risk management as a long – term strategic planning tool - Ramazan, Zh. ("M. Narikbayev KAZGUU University". Nur-Sultan, 2021)
In the modern world, it is difficult to imagine a field of activity in which banks would not take part. The daily tasks facing a person of the 21st century are inextricably linked to interaction with banks, making purchases at points of sale, applying for a mortgage to buy a home or buying a car on credit, and businesses, in turn, have to carry out many operations to transfer funds to pay or receive payments for goods and services. And this is only a small part of what a modern bank has to deal with. All these opportunities are provided to us by banks, and for this reason, banks are an integral part of the life of any economy. As of January 1, 2021, 26 second-tier banks operate in Kazakhstan, including 15 banks with foreign participation and 1 bank with 100% government participation. The banks ' assets, in turn, amount to 31,171. 7 billion tenge, in the structure of which 15,792. 1 billion tenge is the main debt of borrowers, in other words, the loan portfolio. In turn, the deposits of the bank's clients amount to 21,559. 2 billion tenge, thus the share of assets to GDP is 44.7%, the share of the loan portfolio to GDP is 22.6% and the share of deposits to GDP is 30.9% (NBK, 2021). The activities of the banks themselves and their sustainability affect not only the bank's shareholders and their employees, but also customers who have loans and credit lines, deposits and other products of the bank. In addition, loans have a long-term impact on inflation and the economy as a whole. After all, if the effect of the "bubble" that occurred in 2008 due to the mortgage boom is produced, then the country will have a low level of free cash to buy goods and services. In turn, it affects the consumer ability of the population and businesses, thereby reducing the growth of the economy (NBK, 2019). Also, in the period from 2005 to 2007, Kazakhstan's second-tier banks were funded by funds from Europe, which is about 44% of the country's GDP was raised in foreign currency. These funds were mainly directed to retail customers in the form of mortgages, as the requirements became tougher with the onset of the global financial crisis, banks lost access to foreign financing and the non-commodity sector of the economy showed a slowdown in growth (IMF 2014).
Keywords: Kazakhstan's banking sector, financial liquidity, assets liquidity